FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN DUKUNGAN SUAMI TEKAIT PERAWATAN BAYI BARU LAHIR DI UPTD. PUSKESMAS IV DINAS KESEHATAN KECAMATAN DENPASAR SELATAN - Dewi Widiastuti, Ni Putu Gayatri; Widyanthini, Desak Nym (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024, 2025)
Husband's social support is an important aspect for the mother's self-adjustment in undergoing new activities and roles in caring for the baby. This study aims to look at the factors associated with husband support related to newborn care. The study was an observational analytic study using a cross-sectional design. The research sample was the husband who brought his baby aged 0-6 months to do basic immunization at UPTD. Puskesmas IV South Denpasar with a sample size of 100 respondents. The data collection process used consecutive sampling technique with a questionnaire. Data analysis using descriptive tests and Simple Logistic Regression tests. The independent variables of this study were age, education, husband's job, wife's job, number of children, living situation and knowledge. The results of this study found that husbands with 1 child had a 2.42 times better chance of forming good husband support related to newborn care (OR = 2.42; 95%CI 1.08-5.44). Husbands who have good knowledge will have a 3.39 times chance of providing good husband support related to newborn care (OR = 3.39; 95% CI 1.46-7.85). Health services are expected to be able to increase husband involvement through providing education related to child care and parenting so that husbands can provide full support to mothers and babies. Keywords: Husband Support, Newborn Care